2012
DOI: 10.1371/journal.pone.0037151
|View full text |Cite
|
Sign up to set email alerts
|

The SAM Domain of Human TEL2 Can Abrogate Transcriptional Output from TEL1 (ETV-6) and ETS1/ETS2

Abstract: Regulation of gene expression downstream of the Receptor Tyrosine Kinase signaling pathway in Drosophila relies on a transcriptional effector network featuring two conserved Ets family proteins, Yan and Pointed, known as TEL1 (ETV6) and ETS1/ETS2, respectively, in mammals. As in Drosophila, both TEL1 and ETS1/ETS2 operate as Ras pathway transcriptional effectors and misregulated activity of either factor has been implicated in many human leukemias and solid tumors. Providing essential regulation to the Drosoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 30 publications
(68 reference statements)
0
10
0
Order By: Relevance
“…Tribolium ; Bucher and Klingler, 2005 ), echinoderms, and the chordate Ciona . Although no clear ortholog of Edl appears to be present in vertebrates, a SAM domain-only isoform of the human Yan-relative TEL2 as well as Drosophila Edl were shown to inhibit transcriptional stimulation by the mammalian Pnt orthologs ETS1/ETS2 in cell culture ( Gu et al, 2001 ; Vivekanand and Rebay, 2012 ). Hence, the restriction of ETS protein activities by protein-protein interactions offers an intriguing mechanism to fine-tune MAPK signaling output in developing tissues of both invertebrates and vertebrates.…”
Section: Discussionmentioning
confidence: 99%
“…Tribolium ; Bucher and Klingler, 2005 ), echinoderms, and the chordate Ciona . Although no clear ortholog of Edl appears to be present in vertebrates, a SAM domain-only isoform of the human Yan-relative TEL2 as well as Drosophila Edl were shown to inhibit transcriptional stimulation by the mammalian Pnt orthologs ETS1/ETS2 in cell culture ( Gu et al, 2001 ; Vivekanand and Rebay, 2012 ). Hence, the restriction of ETS protein activities by protein-protein interactions offers an intriguing mechanism to fine-tune MAPK signaling output in developing tissues of both invertebrates and vertebrates.…”
Section: Discussionmentioning
confidence: 99%
“…When we analyzed both TFs in the other two species, we only found differential expression of ets2 (Am < Pm; i.e., gradient in the same direction as tel2 ) in the straight-striped M. auratus . Interestingly, TEL2 can suppress ETS2 transcriptional activity and this mechanism appeared to be highly conserved in animal (between Drosophila and human) ( Vivekanand et al, 2012 ). Consequently, in A. christyi , the anterior-posterior variation in tel2 expression might cancel out the variation in ets2 expression, thus making the tel2 / ets2 expression patterns in the two oblique-striped species functionally equivalent.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we found that Hmbox1 positively regulated CD163, while CD163 might be regulated by Ets-2 [ 34 ]. Meanwhile, plenty of reports showed that Ets-1 and Ets-2 are functionally redundant in lots of cases and required for endothelial cell survival [ 35 – 38 ]. It is a possible pathway that CD163 is positively regulated by Hmbox1/Ets-1 signaling, and, in our further investigation, we will verify this pathway of Hmbox1/Ets-1/CD163 signaling.…”
Section: Discussionmentioning
confidence: 99%